2010
DOI: 10.3109/10826084.2010.482449
|View full text |Cite
|
Sign up to set email alerts
|

Fine Mapping of Calcineurin (PPP3CA) Gene Reveals Novel Alternative Splicing Patterns, Association of 5′UTR Trinucleotide Repeat With Addiction Vulnerability, and Differential Isoform Expression in Alzheimer's Disease

Abstract: Fine mapping of calcineurin (PPP3CA) gene identified single nucleotide polymorphisms (SNPs) and simple sequence repeat polymorphisms that are associated with addiction vulnerability. A trinucleotide repeat marker, located in the 5′ untranslated region (5′UTR) of the PPP3CA mRNA, exhibited significantly different genotype and allele frequencies between abusers and controls in the NIDA African-American sample. The polymorphism showed allelic-specific expression in mRNA extracted from postmortem brain specimens. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 26 publications
2
18
0
Order By: Relevance
“…The Chi-square analysis used to determine p values for genotype and allele frequencies returned no statistically significant difference (p > .05) between cases and controls for rs2850328 genotype frequencies (χ 2 = 1.2, p = .5476) and allele frequencies (χ 2 = 0.68, p = .4108) which was a similar finding as Chiocco et al (2010) who also found no significance in the genotype frequencies (p = .968) or the allele frequencies (p = .962) for the same SNP in a population of addiction abusers and healthy controls.…”
Section: Twin Research and Human Genetics December 2011supporting
confidence: 66%
See 2 more Smart Citations
“…The Chi-square analysis used to determine p values for genotype and allele frequencies returned no statistically significant difference (p > .05) between cases and controls for rs2850328 genotype frequencies (χ 2 = 1.2, p = .5476) and allele frequencies (χ 2 = 0.68, p = .4108) which was a similar finding as Chiocco et al (2010) who also found no significance in the genotype frequencies (p = .968) or the allele frequencies (p = .962) for the same SNP in a population of addiction abusers and healthy controls.…”
Section: Twin Research and Human Genetics December 2011supporting
confidence: 66%
“…While the MARK4 rs2395 SNP to our knowledge has not been previously investigated in an association study, the PPP3CA rs2850328 SNP was previously investigated in an association study on addiction vulnerability and differential isoform expression in Alzheimer's disease (Chiocco et al, 2010). In the study, the investigators looked at several PPP3CA SNPs including rs2850328 associated with addiction for an association with Alzheimer's disease.…”
Section: Twin Research and Human Genetics December 2011mentioning
confidence: 99%
See 1 more Smart Citation
“…A detailed analysis has identified a variety of novel PPP3CA variants that can generate a number of splicing isoforms of PP2B that exhibit differential expression in brain and nonbrain tissues. 118 The expression of several of these PPP3CA isoforms, but not all, that encode functional phosphatase domains was found to be decreased in the medial temporal gyrus from AD patient brains.…”
Section: Protein Phosphatase 2b (Calcineurin)mentioning
confidence: 91%
“…PPP3CA encodes the alpha catalytic subunit of a Ca2+/calmodulin-dependent serine/threonine phosphatase, which is also called calcineurin. Genetic alterations in PPP3CA have been previously linked with vulnerability to misuse of multiple substances (Chiocco et al, 2010). It was reported that calcineurin may influence reward-and memory-related phenotypes in addiction thought to link dopaminergic and glutamatergic signals (Chiocco et al, 2010;Gerdjikov & Beninger, 2005).…”
mentioning
confidence: 99%